ANALISIS PERSEPSI KONSUMEN PADA APLIKASI BAURAN PEMASARAN SERTA HUBUNGANNYA TERHADAP LOYALITAS KONSUMEN (STUDI KASUS PADA HYPERMART CABANG KELAPA GADING) - Aristo Surya; Ari Setiyaningrum (Bina Nusantara University, 2009)
Competitive conditions that occur in the retail industry in Indonesia are increasingly tight. Each retail company vying to set the right marketing strategy to attract customers and get as many customer as possible. As one of the largest retail companies that dominate the retail industry in Indonesia, Hypermart need a strategy marketing mix that appropriate to retain existing customers and they wiil not switch to the competitors. The objectives of this study are to analyze how consumers' perceptions of the marketing mix applications in retailing and examined the relationship between consumer perceptions of the marketing mix applications and loyalty. Research conducted at Hypermart Kelapa Gading branch. Research conducted by survey method, which is by distributing questionnaires to 100 consumers who shopped at Hypermart Kelapa Gading branch. The sampling method used in this study is probability sampling. Desciptive statistic method and Cochran's test used to analyze the data. The results indicate that consumer perceptions of the marketing mix adopted by Hypermart Kelapa Gading branch is positive, it means they agree that Hypermart has implemented an appropriate marketing mix and satisfying. The results of Cochran's test analysis found that promotion is not related to loyalty and place has the strongest relationship to the loyalty of consumers shopping at Hypermart.